RANCANG BANGUN SISTEM INFORMASI POSYANDU BERBASIS WEB DI DESA KALIGIRI - Nanda Dimas Arjuwanda; Ryan Fitrian Pahlevi; Abdul Jamil (Politeknik Negeri Indramayu, 2022)
Management of posyandu in Kaligiri village is currently still using conventional systems and not computerized properly, in the sense that they still use manuals and have not used technology in their data collection. This method has many weaknesses, in addition to taking a long time, its accuracy is also not acceptable, because the possibility of error is very large. Based on this, a web-based Posyandu management system in Kaligiri village is needed that is more efficient and well computerized. SDLC is the method used to build a web-based Posyandu information system in Kaligiri village, because this method is effective and efficient in its implementation. A web-based Posyandu information system includes maternal data, child data, officer data, child weighing, child immunization and reports which will be able to input all data using a computerized system to facilitate health cadres. System testing carried out using black box testing by Mr. Kalimi as the Posyandu manager in Kaligiri village proved that the Posyandu information system in Kaligiri village could run well with the acquisition of a percentage of 90% of its success and it is hoped that the management system created can ease the Posyandu manager in Kaligiri village as in making reports, inputing child data, mother data, officer data, weighing children and child immunization at Posyandu Kaligiri.